ANALISIS PERBANDINGAN KURIKULUM EKONOMI SMA HONG KONG DENGAN INDONESIA - Roni Faslah (Jurnal Ilmiah Econosains, 2012)
Abstract Comparative studies of education is one way of knowing various aspects dealing with education city possessed by country other , especially that dealing with excess happened to the system with the various components fans . Important for us to know education system that owned by a country as a comparison and material academic study against education system that we have . In addition , us to have picture of our own position against sitem are we run. Therefore on that occasion writer trying to untwist comparison education curriculum economic in hongkong with indonesia in secondary high school.